2013
DOI: 10.1002/ctpp.201310003
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Plasma Properties Using the Floating Potential of Emissive Langmuir Probes

Abstract: The measurement of the plasma potential of unmagnetized Maxwellian plasmas by using the floating potential of emissive Langmuir probes is discussed. The temperature of the probe was monitored in order to estimate the emitted thermoionic electron current and to determine the limits of the strong electron emission regime. Under these ideal conditions, the measurements of the plasma potential of the emissive probe are cross checked against those of collecting Langmuir probes. In agreement with previous works, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…1 has been previously reported by different authors but has not received a fully satisfactory explanation yet [14]. As proposed in [10], Fig. 5 shows the expression for I co (T p ) that could be approximated by…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…1 has been previously reported by different authors but has not received a fully satisfactory explanation yet [14]. As proposed in [10], Fig. 5 shows the expression for I co (T p ) that could be approximated by…”
Section: Resultsmentioning
confidence: 76%
“…We have concluded that V p \ could be determined by using hot emissive Langmuir probes plotting V F (T P ) as a function of T p (or equivalently, probe heating current In) as discussed in [8]- [10] and [14]. The abrupt change in the slope of V F (T P ) that appears at temperature T ph where V F (T pl ) ~ V ph determines the value of the plasma potential.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, in plasmas is typical to analyse the electrical current density, defined as J γ = [q γ ] = q γ n γ u γ , which is a parameter related to the electrical current measured in laboratories by means of, for example, electrical probes [28,[83][84][85]. In addition, total heat flux can be computed by Q γ = [v 2 ]/2n γ .…”
Section: Kinetic Theory In Plasmasmentioning
confidence: 99%